Impact of COVID-19 infection on cardiorespiratory fitness, sleep, and psychology of endurance athletes- CAESAR Study - Sliz, D.; Wiecha, S.; Gasior, J. S.; Kasiak, P. S.; Ulaszewska, K.; Lewandowski, M.; Barylski, M.; Mamcarz, A. (Journal of Clinical Medicine, 2023)
COVID-19 has a deteriorating impact on health which is especially important for endurance athletes (EAs) who need to maintain continuity of training. The illness affects sleep and psychology, which influence sport performance. The aims of this study were: (1) to assess the consequences of mild COVID-19 on sleep and psychology and (2) to assess the consequences of mild COVID-19 on cardiopulmonary exercise test (CPET) results. A total of 49 EAs (males = 43, 87.76%; females = 6, 12.24%; age = 39.9 ± 7.8 years; height = 178.4 ± 6.8 cm; weight = 76.3 ± 10.4 kg; BMI = 24.0 ± 2.6 kg·m-2) underwent a maximal cycling or running CPET pre- and post-COVID-19 and completed an original survey. Exercise performance deteriorated after COVID-19 (maximal oxygen uptake, VO2max = 47.81 ± 7.81 vs. 44.97 ± 7.00 mL·kg·min-1 pre- and post-infection, respectively; p < 0.001). Waking up at night affected the heart rate (HR) at the respiratory compensation point (RCP) (p = 0.028). Sleep time influenced pulmonary ventilation (p = 0.013), breathing frequency (p = 0.010), and blood lactate concentration (Lac) (p = 0.013) at the RCP. The maximal power/speed (p = 0.046) and HR (p = 0.070) were linked to the quality of sleep. Stress management and relaxation techniques were linked with VO2max (p = 0.046), maximal power/speed (p = 0.033), and maximal Lac (p = 0.045). Cardiorespiratory fitness deteriorated after mild COVID-19 and was correlated with sleep and psychological indices. Medical professionals should encourage EAs to maintain proper mental health and sleep after COVID-19 infection to facilitate recovery.